Klimawandel und Gender Untersuchung der Bedeutung von Geschlecht für die soziale Vulnerabilität in überflutungsgefährdeten Gebieten - Chávez Rodríguez, Libertad (2013)
Gender and Disasters, Doing Gender, Intersectionality, Social Vulnerability, Disaster Risk Management, Floods, Mexico, Germany. - The dissertation examines the significance of gender and gender relationships in connection with other socio-economic characteristics for the social vulnerability to climate change-related extreme weather events. What options for environmental political action for DRM can be derived from the answers to that question? Empirical research was conducted in two flood prone areas, in the Elbe riverside region of Low Saxony, Germany and in the northern coast of Yucatán, Mexico. The collection of empirical data included primarily expert interviews and focus groups with population affected by floods. The dissertation is situated in the gender and environment' research field and places a focus on climate change. It addresses a thematic with significant research needs and a clear lack of empirically grounded data. It works out gender-related blind spots in the concept of social vulnerability, contributing to the further development of a relevant concept to the consequences of climate change.
Keywords: Klimaänderung; Überschwemmungsgefahr; Geschlechtsunterschied; Hochschulschrift